Transport Cost Sharing and Spatial Competition - Hrachya Kyureghian; Sudipta Sarangi (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
We consider a linear city model where both firms and consumers have to incur transport costs. Following a standard Hotelling (1929) type framework we analyze a duopoly where firms facing a continuum of consumers choose locations and prices, with the transportation rate being linear in distance. From a theoretical point of view such a model is interesting since mill pricing and uniform delivery pricing arise as special cases. Given the complex nature of the profit function for the two-stage transport cost sharing game, we invoke simplifying assumptions and solve for two different games. We provide a complete characterization for the equilibrium of the location game between the duopolists by removing the price choice from the strategy space. We then find that if the two firms are constrained to locate at the same spot, the resulting price competition leads to a mixed strategy equilibrium with discriminatory rationing. In equilibrium both firms always have positive expected profits. Finally, we derive a pure strategy equilibrium for the two-stage game. Results are then compared with the mill pricing and uniform delivery pricing models.
Keywords: C72; D43; L13; R1; 330; Spatial Competition; Cost Sharing; Hotelling Modell; Räumlicher Wettbewerb; Transportkosten; Nichtkooperatives Spiel; Theorie; cost sharing